Efektivitas Pelayanan Aktivasi Identitas Kependudukan Digital di Balai RW Kelurahan Medokan Ayu - Vitantyo, Batara Bintang; Prathama, Ananta (VISA: Journal of Vision and Ideas, 2025)
Indonesia has entered the era of digitalization, where the development of technology and information is accelerating. Of course, the development of technology and information has an impact on various aspects, one of which is the aspect of public services by the government in the field of public services through the Digital Population Identity or IKD program. The Digital Population Identity program is an innovation carried out by the Directorate General of Dukcapil of the Ministry of Home Affairs to simplify and accelerate the process of digital public service transactions. The establishment of Digital Population Identity can be done in various locations, including Siola, Sub-district, Village Office, and RW Hall. This study aims to conduct an in-depth analysis of the effectiveness of the IKD activation service at the Medokan Ayu Village RW Hall in helping residents activate IKD. This research uses a qualitative methodology with a descriptive approach. The data used in this research comes from primary and secondary references, with primary data obtained through observation and documentation techniques, while secondary data is obtained through a literature review. The theoretical framework used in this research is the theory of effectiveness which includes four main indicators, namely the accuracy of program targets, program socialization, achievement of program objectives, and program monitoring. The results of this study show that residents are very enthusiastic in activating IKD at the RW Hall of Medokan Ayu Village. The socialization of the IKD activation service program at Balai RW was carried out by the Medokan Ayu Village Government in collaboration with the Heads of RT and RW. In its implementation, there are still obstacles in implementing the program. Monitoring is carried out by Medokan Ayu Village and Surabaya City Civil Registration and Population Office employees, and the monitoring results are used as evaluation material.